THE IMPOSITION OF GOGOLI PENALTY AS AN EFFORT TO ERADICATE CORRUPTION BASED ON LOCAL WISDOM (A STUDY OF THE REIGN OF BUTON SULTANATE) - Muh Sutri Mansyah (Asia Pacific Fraud Journal, 2018)
Nowadays, Indonesia is undergoing a corruption problem unresolved. a variety of efforts to combat corruption a criminal offence has been committed, but not yet scrapped in law enforcement. as can be eradicated up to its roots, it is to be one of the barriers that were experienced by our law enforcement officers, the overthrow of criminal sanctions as deterrent effects do not cause against the corruptor, then should the overthrow criminal sanctions heavier again. As well as administering Gogoli penalty or death sentence applied in the Sultanate of Buton at the time of his reign, but in execution i.e. a rope twirled and drawn in a manner opposite direction until a dead, Surely the concept of the overthrow of the current criminal sanctions imposed during the reign of the Buton Sultanate. pose a deterrent effect and a structural officials have feelings of fear to commit irregularities such as corruption, then the author represents the hope that the punishment could be applied nationally Gogoli considering the criminal act corruption happens almost throughout the regions and regional officials who are often exposed to cases of criminal acts of corruption.